PELATIHAN BATIK LILIN DINGIN DENGAN VISUAL CIRI KHAS BETAWI DI RUMAH SINGGAH BINA ANAK PERTIWI JAKARTA - Gilang Cempaka; Ayoeningsih Dyah (LPPM UPN Veteran Jakarta, 2021)
Community service by Visual Communication Design (DKV) Paramadina University is aims to developing skills for the member of residents at the “Rumah Singgah” Bina Anak Pertiwi. It has around 166 children and 377 adults. They generally come from street who do not have a decent life. The training is taught batik through cold wax media on cloth, with visual characteristics of Betawi culture. DKV empowering member of residents through improving skills in batik. Besides abilities in digital technology, hand skills with creativity are believed still survive and become the backbone of the creative industry in the 4.0 era. The activity method is to provide training with practicing, apply cold waxed batik with the visuals of Betawi’s icons. This activity was attended by around fifteen member residents. Through this training, batik can be developed into various kinds of products such as scarves, tablecloths, souvenirs and other home decorations. Making batik with cold wax is relatively easy to apply, and the materials are easy to get. So it is hoped that the member residents can innovatively develop their own skills and creativity. They are expected to be more productive so that they can improve their economic level.